Safety and Efficacy of Intravitreal Chemotherapy (Melphalan) to Treat Vitreous Seeds in Retinoblastoma - Yousef, Yacoub A.; Al Jboor, Mays; Mohammad, Mona; Mehyar, Mustafa; Toro, Mario D.; Nazzal, Rashed; Alzureikat, Qusai H.; Rejdak, Magdalena; Elfalah, Mutasem; Sultan, Iyad; Rejdak, Robert; Al-Hussaini, Maysa; et al. (Frontiers in Pharmacology, 2021)
Background: Active vitreous seeds in eyes with retinoblastoma (Rb) adversely affects the treatment outcome. This study aimed to investigate the safety and efficacy of intravitreal melphalan chemotherapy (IViC) as a treatment for recurrent and refractory vitreous seeds in patients with Rb. Methods: A retrospective non-comparative study of patients with intraocular Rb who had vitreous seeds and treated by IViC (20-30µg of melphalan) using the safety-enhanced anti-reflux technique. Tumor response, ocular toxicity, demographics, clinical features, and survival were analyzed. Results: Twenty-seven eyes were treated with 108 injections for recurrent (16 eyes) or refractory (11 eyes) vitreous seeds after failed systemic chemotherapy. Fifteen (56%) were males, and 20(74%) had bilateral disease. At diagnosis, majority (n=21) of the injected eyes were group D and n=6 were group C. Vitreous seeds showed complete regression in 21(78%) eyes; 100% (n=10) for eyes with focal seeds and 65% (n=11/17 eyes) for eyes with diffuse seeds (p=0.04). Seven (64%) eyes with refractory seeds and 14 (87%) eyes with recurrent seeds showed complete response (P=0.37). Sixteen (59%) eyes developed side effects; retinal toxicity (48%), pupillary synechiae (15%), cataracts (30%), iris atrophy (7%), and retinal and optic atrophy (4%). Only one child was lost to follow-up whose family refused enucleation and none developed orbital tumor recurrence or distant metastasis. Conclusion: IViC with melphalan is effective (more for focal than diffuse seeding) and a relatively safe treatment modality for Rb that can improve the outcomes of eye salvage procedures. However, unexpected toxicity can occur even with the standard dose of 20-30 µg.